The relationship between SCM digitalization and earnings management: The case of Moroccan companies listed on the Casablanca stock exchange - BELLARI, Mounir; AMRAOUI, Hanane EL (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of digitalization in Supply Chain Management (SCM) on earnings management practices among Moroccan listed companies. Using a sample of 48 non-financial firms over the period 2016–2023, it examines how three key digital SCM tools, Enterprise Resource Planning (ERP), Electronic Data Interchange (EDI), and Digital Tracking Systems (DTS) influence the extent of discretionary accruals as a proxy for earnings management. Relying on panel logistic regression models with robust standard errors, the findings reveal that ERP adoption and digital tracking technologies significantly reduce earnings management, thereby enhancing financial transparency and information reliability. These results support the assumptions of agency theory, transparency theory, and institutional theory, which suggest that digitalization can mitigate information asymmetry and opportunistic managerial behavior. However, EDI use exhibits no significant relationship, indicating that its impact depends on the level of technological integration and organizational maturity. Overall, this study contributes to the emerging literature on digital transformation and financial governance by providing empirical evidence from an emerging market context, emphasizing how SCM digitalization fosters ethical reporting and strengthens corporate accountability in Morocco.